52P Chronic and late-onset toxicities from immune checkpoints inhibitors (ICIs): Analysis of the publications leading to ICIs approval between 2011 and 2019. (15th December 2019) - Ghisoni, E; Marandino, L; Valabrega, G; Aglietta, M; Di Maio, M
Abstract: Background: Immune checkpoints inhibitors (ICIs) are receiving approval for a growing number of indications. Even if generally well-tolerated, ICIs can cause rare but severe immune-related adverse events (irAEs) with late onset and long-term impact. Aim of this analysis was to evaluate the completeness of irAEs description, with particular attention to irAEs duration and occurrence of late toxicities, in ICIs pivotal trials. Methods: We analysed the publications corresponding to the studies leading to ICIs approval by US Food and Drug Administration (FDA) and/or European Medicines Agency from March 2011 up to August 2019. We searched for duration of follow-up, proportion of patients still on treatment at data cut-off, duration of irAEs and proportion of patients with unresolved toxicities at data cut-off. Results: Overall, we found 58 publications, corresponding to 49 trials (table ). Among all studies, median follow-up was 13, 5 months (interquartile range [IQR] 5, 8–14, 9), and it was 10, 2 months (IQR 5 -11, 9) for the ones which led to ICIs approval with FDA fast-track procedure versus 15, 2 months (IQR 12-16, 2) for those leading to ICIs approval through regular procedure (p < 0.001). In 40/58 publications (68, 9%), a mean of 22, 4% of patients (range 1%-63%) were still ongoing at data cut-off; in 10/58 (17, 2%) data were not reported. Duration of irAEs and proportion of patients with unresolved toxicities at data cut-off were not specified in 52 publications (89, 6%). In 6 publications with available data, 3% to 66% of patients had still ongoing irAEs. Secondary publications were available in 15/58 cases (25, 8%) and showed that even at longer follow-up (median 24.2 months), the proportion of patients still on treatment at data cut-off was not negligible (7.3%-32%) and only 3/15 studies (20%) presented an update regarding duration of irAEs. Conclusion: Description of toxicity in publications of clinical trials of ICIs is often suboptimal especially in terms of duration and long-term sequelae. Future efforts should focus on capturing the real impact of irAEs on patients' QoL to better define treatments value. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: G. Valabrega: Honoraria (self): Roche; Honoraria (self): Amgen; Honoraria (self): AstraZeneca; Honoraria (self): PharmaMar; Honoraria (self): Tesaro. M. Aglietta: Honoraria (self): Tesaro; Honoraria (self): Roche; Honoraria (institution): AstraZeneca. M. Di Maio: Honoraria (institution): Tesaro; Honoraria (self): Bristol Meyers Squibb; Honoraria (self): Roche; Honoraria (self): AstraZeneca; Honoraria (self): Takeda; Honoraria (self): Janssen. All other authors have declared no conflicts of interest.